PENGGUNAAN MEDIA BERBASIS ICT BAAMBOOZLE UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA DI SMPN 24 MEDAN TAHUN PELAJARAN 2025/2026 - Marly Meani Silalahi; Hapni Laila Siregar; Reh Bungana Beru Parangin-angin; Abdinur Batubara; Oksari Anastasya Sihaloho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the effectiveness of using Baamboozle, an ICTbased learning media, in enhancing students' cognitive learning outcomes in Pancasila Education. The primary problem addressed in this study is the low level of student learning achievement, where 60.3% of students have not reached the Minimum Mastery Criterion (KKM) due to the dominance of conventional teaching methods. This study is quantitative in nature, employing a quasi-experimental method with a nonequivalent control group design. The research population comprised 320 students, with samples taken from classes VII-G (experimental) and VII-F (control), each consisting of 32 students selected via purposive sampling. Data were gathered through tests (pre-test and post-test), perception questionnaires, and observations, followed by analysis using independent sample t-tests and N-Gain Score calculations facilitated by SPSS 25. The results indicate a significant effect of using Baamboozle media on student learning outcomes, with a significance value (Sig. 2-tailed) of 0.000 < 0.05. The average post-test score for the experimental class (86.05) was significantly higher than that of the control class (73.99). N-Gain analysis showed that the experimental class's effectiveness reached 0.66 (Moderate/Fairly Effective Category), whereas the control class only reached 0.33 (Low Category). Additionally, student perceptions of Baamboozle media fell into the very strong category, with percentages exceeding 90% across all dimensions. In conclusion, Baamboozle media is effective in improving cognitive learning outcomes and active student engagement in Pancasila Education learning.